Implementasi Sistem Manajemen Kesehatan dan Keselamatan Kerja (SMK3) di PT. Pelindo Marine Service - Widodo, Nurul Sapta; Kristiawan, Dedy (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2020)
The purpose of this study was to describe and analyze the implementation of SMK3 and the factors that support and hinder the implementation of SMK3 at PT. Pelindo Marine Service. The method for obtaining in-depth interview informants was carried out by purposive sampling, with the research informants being parties with the authority and knowledge regarding the implementation of K3 at PT. PMS. As an instrument, researchers are directly involved in participatory observation and the informant elements are the Board of Directors, the K3 Section, and the Workers. Obtained the level of achievement of the implementation of an advanced level of K3 Management System at PT. Pelindo Marine Service (Persero) Surabaya Container Terminal, namely 83%. For aspects of the Bureaucratic Structure of PT. Pelindo Marine Service (Persero) Surabaya Container Terminal is able to implement an OHS management system that can integrate with company management. For the Disposition aspect of PT. Pelindo Marine Service (Persero) Terminal Petikemas Surabaya has an updated K3 policy and written commitment which has been submitted to top management. For the resource aspect of PT. Pelindo Marine Service (Persero) Surabaya Container Terminal already has a P2K3 team with P2K3 secretaries who have been certified as general K3 experts in accordance with the regulations and laws and representatives of K3 experts from each division. For the communication aspect of PT. Pelindo Marine Service (Persero) Surabaya Container Terminal between the management and other parties in the company is carried out verbally or correspondingly. Visitors must follow the safety induction before entering the customs area. The K3 management system implementation model consists of aspects that support the achievement of implementation based on the objectives of the K3 management system.